2017
DOI: 10.1016/j.ijid.2017.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Are antibiotic-resistant pathogens more common in subsequent episodes of diabetic foot infection?

Abstract: After the successful treatment of a DFI, recurrent episodes are frequent. A history of a previous DFI episode did not predict a greater likelihood of any antibiotic-resistant isolate in subsequent episodes. Thus, broadening the spectrum of empiric antibiotic therapy for recurrent episodes of DFI does not appear necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 16 publications
3
40
0
1
Order By: Relevance
“…Fourthly, we defined remission as the absence of any clinical, radiological or laboratory signs of recurrent or new DFI at the site of prior infection, within one year following treatment of the prior DFI episode. In DFI, microbiological patterns of consecutive DFI episodes are only congruent in two‐thirds of cases at most, and new ischaemia, noncompliance, as well as inadequate anatomical positioning may lead to new infections at the same location. Hence, we overestimate the true risk of recurrence having more to do with patient's compliance or progressive ischaemia rather than with antibiotic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Fourthly, we defined remission as the absence of any clinical, radiological or laboratory signs of recurrent or new DFI at the site of prior infection, within one year following treatment of the prior DFI episode. In DFI, microbiological patterns of consecutive DFI episodes are only congruent in two‐thirds of cases at most, and new ischaemia, noncompliance, as well as inadequate anatomical positioning may lead to new infections at the same location. Hence, we overestimate the true risk of recurrence having more to do with patient's compliance or progressive ischaemia rather than with antibiotic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Lebowitz and co-workers followed 482 subjects for a median of 3.3 years after the first occurrence of diabetic foot infections and noted 2,257 total episodes of infection with a median of 7.6 months interval between recurrent episodes. 16 The causative pathogens was noted to be the same as in previous episodes in 43% of recurrent cases with no significant increase in the incidence of antibiotic resistance over the episodes. 16 The authors concluded that previous diabetic foot infection episodes did not predict a greater likelihood of antibiotic-resistant isolate in subsequent episodes, and broadening the spectrum of empiric antibiotic therapy for recurrent episodes of diabetic foot infections did not appear necessary.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 67%
“…16 The causative pathogens was noted to be the same as in previous episodes in 43% of recurrent cases with no significant increase in the incidence of antibiotic resistance over the episodes. 16 The authors concluded that previous diabetic foot infection episodes did not predict a greater likelihood of antibiotic-resistant isolate in subsequent episodes, and broadening the spectrum of empiric antibiotic therapy for recurrent episodes of diabetic foot infections did not appear necessary. 16 Needless to say, larger studies are needed to confirm or refute these findings.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 67%
“…Staphylococcus aureus is consistently the most prevalent species (>50% of all wounds), followed by coagulase‐negative Staphylococci spp. and Streptococcus spp . S. aureus , including methicillin‐resistant S. aureus (MRSA), is often found in association with other Gram‐positive pathogens and mixed anaerobic communities, but not Pseudomonas aeruginosa , a common misconception .…”
Section: Culture‐based Characterization Of Chronic Wound Microbiomesmentioning
confidence: 99%
“…and Streptococcus spp. [47][48][49][50] S. aureus, including methicillin-resistant S. aureus (MRSA), is often found in association with other Grampositive pathogens and mixed anaerobic communities, but not Pseudomonas aeruginosa, a common misconception. [51][52][53] Because of P. aeruginosa's ability to form the archetypal mushroom-like biofilm colonies encapsulated in a protective extracellular matrix in vitro, it has been studied as a model organism of biofilm formation.…”
Section: Culture-based Characterization Of Chronic Wound Microbiomesmentioning
confidence: 99%